Developing a framework for the internationalization of British Healthcare institutes: A qualitative dual case study analysis. (April 2014) - Siddiqui, Samee; Ramesh, Anand; Manoharan, Karthick; Hussein, Annas; Jawad, Ali M.; Hussain, Farhan
<x content-type="archive" xml:space="preserve">Abstract</x> Internationalization of healthcare represents an exciting strategic opportunity, offering new revenue streams to western health institutes experiencing declining growth potential in their current markets. British healthcare institutes stand to gain significantly from this, but currently lack significant presence and experience in the international sphere. We conducted a qualitative case study analysis of Moorfields Eye Hospital Dubai and Imperial College Diabetes Centre, Abu Dhabi, the only two British institutes to have internationalized thus far, to identify key strategic factors for successful overseas expansion. This involved a literature review, semi-structured interviews with top management personnel, and review of official documentation from each institute. Analysis of our findings led to the creation of the Drivers Region Management strategic considerations model, integrating the key factors identified, as a means of systematically guiding decision-making for future internationalization attempts. This will be further refined with stakeholder input and comparison with other countries, with the ultimate aim of developing a generalizable tool for British healthcare institutes.